Analisis Strategi Bisnis Menggunakan SWOT, BMC, dan Balance Scorecard pada UMKM AC - Shafa Nabila; Febriana Nur Aulia; Annisa Mulia Bakti; Khansa Aristya Pramesti; Indy Tsamara Zahra; Lindawati Kartika (Lembaga Pengembangan Kinerja Dosen, 2024)
The food and beverage industry contributes significantly to Indonesia's Gross Domestic Product (GDP), with UMKM AC, located in Bogor City, being one of the contributors. This research formulates a business strategy for UMKM AC using the Business Model Canvas (BMC), SWOT analysis, and evaluation of Key Performance Indicators (KPIs) with the Balanced Scorecard (BSC). Data were collected through questionnaires and literature studies. The BMC analysis results indicate strengths in customer segmentation and community relations. The internal and external factor analysis shows that UMKM AC is in a position to grow and develop. The SWOT analysis identifies opportunities for UMKM AC, focusing on strategies that have a positive impact. The BSC evaluation shows overall good performance, but there are some strategic goals that need further improvement. This research highlights the importance of strategic planning and performance evaluation for SMEs in facing industry competition.